People with high empathy show increased cortical activity around the left medial parieto-occipital sulcus after watching social interaction of on-screen characters. (20th January 2022) - Hamada, Masayoshi; Matsubayashi, Jun; Tanaka, Kenta; Furuya, Makiko; Matsuhashi, Masao; Mima, Tatsuya; Fukuyama, Hidenao; Mitani, Akira
Abstract: People with high empathy interpret others' mental states in daily social interactions. To investigate their characteristics of social cognitive processing, we compared neuromagnetic activities between 20 males with high empathy and 23 males with low empathy while watching social interactions between two characters. Twenty stories of four-panel comic strips were presented; the first three panels described social interactions, and the last panel described empathic/nonempathic behaviors. People with high empathy exhibited increased cortical activity in the right occipital region, medial part of the bilateral superior frontal gyri, and right posterior insula while watching social interaction scenes, which suggests that they paid attention to others' faces and bodies, and inferred others' mental states. They also exhibited increased cortical activity in the left superior frontal gyrus while watching empathic behaviors. Moreover, they exhibited increased cortical activity in the region around the left medial parieto-occipital sulcus, which is related to self-projection, while passively watching both empathic and nonempathic endings. Taken together, these results suggest that people with high empathy pay attention to others and actively infer others' mental states while watching social interactions and that they reconstruct others' mental states and intentions through self-projection after watching a sequence of others' behaviors.